The Efficacy, Safety, and Tolerability of Probiotics on Depression: Clinical Results From an Open-Label Pilot Study - Wallace, Caroline J. K.; Milev, Roumen V. (Frontiers in Psychiatry, 2021)
Background: A growing body of research has shown that consumption of probiotics can improve symptoms associated with mood and anxiety disorders through activity of the gut-brain axis. However, the effects of probiotics have yet to be tested in a clinical sample of treatment-naïve patients diagnosed with Major Depressive Disorder (MDD). The aim of this 8-week, open-label pilot study is to examine changes in depressive symptoms before and after the introduction of a probiotic supplement in 10 treatment-naïve MDD patients and to provide data on the feasibility of conducting a larger double-blind, randomized, placebo-controlled trial in the same patient population. Here we report on the clinical outcome measures of the study. Methods: Participants recruited from the community in Kingston, Ontario, Canada consumed a probiotic supplement containing Lactobacillus helveticus R0052 and Bifidobacterium longum R0175 (CEREBIOME®) at a dose of 3x109 CFU once per day for 8 weeks. Clinical symptoms of depression were measured using a validated battery of clinical scales and self-report questionnaires (CAN-BIND protocol). Data was collected at baseline, week 4, and week 8. Results: Significant improvements in affective clinical symptoms were observed at week 4 and were sustained at week 8. Significant improvements in subjective sleep quality were observed by week 8. No side effects or adverse effects associated with the probiotic supplement were observed. Conclusions: The findings from this study support the existing evidence in this emerging field for probiotics having a role in alleviating symptoms of depression in treatment-naïve, moderately depressed patients and indicate that the probiotic supplement is safe and well-tolerated in this population. However, further comprehensive studies are required to draw conclusions.